FUZZY TRANPORTATION MODEL USING L-R FLAT TRAPEZOIDAL APPROXIMATIONS - Ch.Uma Swetha, N.Ravi Shankar,B.Pardha Saradhi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transportation problem is applied for many differentcircumstances being scheduling,production, investment, plant location, inventory control, employment scheduling, and several methods. The aim of the fuzzy transportation problem is to resolve the transport schedule that minimizes the total fuzzy transportation cost while delightful the fuzzy supply and fuzzy demand limits. In view of this, a novel approach to optimize fuzzy transportation modelby using trapezoidal approximations of L-R flat fuzzy numbers is proposed. A few generalized and modern properties of the trapezoidal and triangular approximations of L-R flat fuzzy numbers forparameters in fuzzy transportation problem is suggested. Numerical example is illustrated for the novel fuzzy transportation model.